LAND-SEA INTERACTIONS IN COASTAL WATERS OFF NE KALIMANTAN: EVIDENCE FROM MICROFAUNAL COMMUNITIES - Kresna Tri Dewi; Noor C.D. Aryanto; Yogi Noviadi (Marine Geological Institute of Indonesia, 2007)
Microfauna (ostracoda and foraminifera) as component of sediments has been used to detect the dynamics of sea floor condition in NE Kalimantan, particularly off Nunukan and Sebatik Islands. In general, the microfaunal components tend to increase (both number of species and specimens) from near shore to the open sea. The microfauna occur rarely at locations surrounding the islands due to high content of plant remains from the land. The marine origin of microfaunas occurs very abundantly in the inner part of the study area between Tinabasan and Nunukan Islands. This finding is interested due to their occurrence as unusual forms: brownish shells, broken and articulated ostracod carapaces. Additional interested findings are: the incidence of abraded test of Elphidium, the occurrence of dominant species of both ostracoda and foraminifera at some stations; various morphological forms of foraminiferal genus, Asterorotalia that reaches about 1% and distributed in the open sea. The various unusual forms may relate to the dynamics of local environmental changes such as postdepositional accumulation in the sediment, biological activities, and drift currents from open sea to landward. Keywords: Ostracoda, Foraminifera, North East Kalimantan, land-sea interaction Mikrofauna (ostracoda dan foraminifera), sebagai komponen sedimen dapat digunakan untuk mendeteksi dinamika kondisi dasar laut di Kalimantan Timur, tepatnya di sekitar Pulau Nunukan dan Sebatik. Secara umum, komponen mikrofauna cenderung bertambah (baik dalam jumlah spesies maupun spesimen) dari perairan sekitar pantai ke arah laut lepas. Mikrofauna yang ditemukan sangat jarang di lokasi sekitar pulau-pulau disebabkan oleh keterdapatan sisa-sisa tanaman dari daratan. Mikrofauna asal lautan ditemukan sangat melimpah di bagian dalam daerah penelitian antara Pulau Tinabasan dan Nunukan. Temuan ini sangat menarik karena adanya bentukan abnormal: cangkang berwarna kecoklatan, rusak dan cangkang ostracoda berbentuk tangkupan. Temuan tambahan yang juga menarik adalah: keterdapatan cangkang Elphidum yang rusak, keterdapatan beberapa spesies ostracoda dan foraminifera secara dominan di titik lokasi tertentu, dan kenampakan morfologi yang bervariasi dari genus foraminifera, Asterorotalia, yang mencapai 1% dan tersebar di laut lepas. Berbagai bentukan abnormal tersebut kemungkinan berkaitan dengan dinamika kondisi lingkungan setempat seperti akumulasi setelah pengendapan dalam sedimen, aktivitas biologis dan alur arus dari laut terbuka kearah daratan. Kata kunci: ostracoda, foraminifera, Kalimantan Timur, interaksi daratan-lautan